All‐Metal Clusters that Mimic the Chemistry of Halogens. Issue 14 (8th August 2013) - Zhao, Tianshan; Li, Yawei; Wang, Qian; Jena, Puru
Abstract: Owing to their s 2 p 5 electronic configuration, halogen atoms are highly electronegative and constitute the anionic components of salts. Whereas clusters that contain no halogen atoms, such as AlH4, mimic the chemistry of halogens and readily form salts (e.g., Na + (AlH4 ) − ), clusters that are solely composed of metal atoms and yet behave in the same manner as a halogen are rare. Because coinage‐metal atoms (Cu, Ag, and Au) only have one valence electron in their outermost electronic shell, as in H, we examined the possibility that, on interacting with Al, in particular as AlX4 (X=Cu, Ag, Au), these metal atoms may exhibit halogen‐like properties. By using density functional theory, we show that AlAu4 not only mimics the chemistry of halogens, but also, with a vertical detachment energy (VDE) of 3.98 eV in its anionic form, is a superhalogen. Similarly, analogous to XHX superhalogens (X=F, Cl, Br), XAuX species with VDEs of 4.65, 4.50, and 4.34 eV in their anionic form, respectively, also form superhalogens. In addition, Au can also form hyperhalogens, a recently discovered species that show electron affinities (EAs) that are even higher than those of their corresponding superhalogen building blocks. For example, the VDEs of M(AlAu4 )2 − (M=Na and K) and anionic (FAuF)Au(FAuF) range from 4.06 to 5.70 eV. Au‐based superhalogen anions, such as AlAu4 − and AuF2 −, have the additional advantage that they exhibit wider optical absorption ranges than their H‐based analogues, AlH4 − and HF2 − . Because of the catalytic properties and the biocompatibility of Au, Au‐based superhalogens may be multifunctional. However, similar studies that were carried out for Cu and Ag atoms have shown that, unlike AlAu4, AlX4 (X=Cu, Ag) clusters are not superhalogens, a property that can be attributed to the large EA of the Au atom. Abstract : Sincerest form of flattery: The frontier orbitals and optical absorption spectra of the AlAu4 − anion are reported. By using density functional theory, it is shown that AlAu4 not only mimics the chemistry of halogens, but also, with a vertical detachment energy (VDE) of 3.98 eV in its anionic form, that it is a superhalogen.